Persistent hypocomplementemia in a 9 year old boy following acute poststreptococcal glomerulonephritis - Ali Derakhshan (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Acute  post-streptococcal  glomerulonephritis  (APSGN)  is  a common  form  of  acute glomerulonephritis  in  children  [1].  It is  presented  with  edema,  hematuria,  acute  renal  failure  and hypertension and hypocomplementemia 7-10days following agroup  a -hemolytic  streptococcal  pharyngitis  or  2-4  weeks following an impetigo [2-4]. Subclinical forms are common in close  contacts  [5-7].  APSGN  usually  is  a  self-limiting  disease and  only  requires  conservative  therapy  for  complications  of acute  kidney  injury  and  also  management  of  hypertension. Severe  cases  may  occur  with  a  rapidly  progressive  course (rapidly progressive glomerulonephritis RPGN) [8], which may need  kidney  biopsy  and  pulse  therapy  with  corticosteroids. Alternate pathway activation and depression of C3 is the usual mechanism  but  in  some  cases  there  may  be  activation  of classic  pathway  [4].  C3  Complement  returns  to  normal  level within 8 weeks. In our case despite a usual feature APSGN and spontaneous  resolution  of  nephritis  C3  is  still  low  even  after 5.5 years.